(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
Currently, economic efficiency is an urgent problem for all industrial enterprises. Due to an increase in the economic efficiency of the diethylene glycol desalination process at natural gas purification and drying units in underground gas storages located on the territory of our republic, 197,667,000.00 sum will be saved annually. The increase in economic efficiency is an urgent problem